2015
DOI: 10.3233/pnr-14088
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and DTI metrics changes in children with cerebral palsy following therapy

Abstract: It is known that patients with chronic hypoxia have regional changes in their cerebral blood flow (CBF). The purpose of this study was to observe the CBF and diffusion tensor imaging (DTI) metrics changes in children with cerebral palsy (CP) at baseline and after 6 months of treatment. Thirty-eight children with cerebral diplegia (mean age = 6.4 yr) and twenty-one age/sex matched controls (mean age = 7.5 yr) were evaluated by the Gross Motor Function Classification System (GMFCS) scoring of motor disability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Moderate to significant improvement in functional abilities. (Jain et al, 2014) No significant change in white matter connectivity. Improvement in GMFCS scores.…”
Section: Results Of Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Moderate to significant improvement in functional abilities. (Jain et al, 2014) No significant change in white matter connectivity. Improvement in GMFCS scores.…”
Section: Results Of Studiesmentioning
confidence: 98%
“…We calculated dose of intervention [dose = duration in weeks * number of sessions per week * length of each session in minutes] for each study and converted that to hours for easier interpretation. Seven studies on children with CP and apraxia didn't provide sufficient information to calculate intervention dose (Jain et al, 2014; Kadis et al, 2014; Kim et al, 2015; Englander et al, 2015; Phillips et al, 2007; Sutcliffe et al, 2009; Baek et al, 2013). Across the remaining 20 studies that reported intervention details, participants received an average of 54.81 h of intervention (intervention range: 3–200 h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resting state motor networks were shown to be altered in both unilateral and bilateral CP, with greater change in the non-dominant hemisphere in unilateral CP 171 . Perfusion MRI was also used to show that regions with diffusion MRI changes demonstrate reduced perfusion 189 .…”
Section: Diffusion Mri Used In Conjunction With Other Imaging Modalitiesmentioning
confidence: 99%